2017
DOI: 10.2967/jnumed.117.201749
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-11 PET/CT Mapping of Prostate Cancer Biochemical Recurrence After Radical Prostatectomy in 270 Patients with a PSA Level of Less Than 1.0 ng/mL: Impact on Salvage Radiotherapy Planning

Abstract: Target volume delineations for prostate cancer (PCa) salvage radiotherapy (SRT) after radical prostatectomy are usually drawn in the absence of visibly recurrent disease. Ga-labeled prostate-specific membrane antigen (PSMA-11) PET/CT detects recurrent PCa with sensitivity superior to standard-of-care imaging at serum prostate-specific antigen (PSA) values low enough to affect target volume delineations for routine SRT. Our objective was to map the recurrence pattern of PCa early biochemical recurrence (BCR) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
201
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(226 citation statements)
references
References 47 publications
19
201
3
3
Order By: Relevance
“…Eighteen studies reported the detection rate of 68 Ga‐PSMA PET in patients with a PSA 0.20–0.49 ng/mL . Combined, this involved 1078 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen studies reported the detection rate of 68 Ga‐PSMA PET in patients with a PSA 0.20–0.49 ng/mL . Combined, this involved 1078 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 567 patients, 367 (64.7%) had a positive 68 Ga‐PSMA PET. The detection rate ranged from 25% to 87.5% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year free-fromprogression rate of patients receiving prostate bed RT, prostate bed RT with short-term ADT, and prostate bed RT with WPRT and short-term ADT were 71%, 81%, and 87%, respectively, all of which were statistically significant. Meanwhile, considering the prevalence of advanced imaging techniques such as prostate specific membrane antigen scans and Axumin positron emission tomography, we believe patients originally defined as postoperative biochemical failure were found to have a high incidence of pelvic lymph node metastasis by these advanced images, 20,21 and therefore, use of WPRT might need additional justification.…”
Section: Discussionmentioning
confidence: 99%
“…It is a type II membrane protein, which is highly expressed in most prostate cancers . It is not secreted and is membrane bound, making it an attractive extracellular target for therapeutic probes for prostate cancer . In clinical studies, Lutetium 177 (Lu) labeled PSMA peptides have already proved to be effective in targeted radionuclide therapy of prostate cancer .…”
mentioning
confidence: 99%